Comparing Participants’ Satisfaction with Behavioral Therapies for Chronic Insomnia - Sidani, Souraya; Epstein, Dana R.; Fox, Mary; Collins, Laura (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2018)
Introduction. Extensive evidence supports the effectiveness of behavioral therapies for chronic insomnia, but there is limited information on patients’ satisfaction with these, which is a key factor in therapy uptake, adherence and effectiveness. Objective. This study compared participants’ satisfaction with the process and outcome attributes of single- and multi-component behavioral therapies for chronic insomnia. Methods. Data were obtained from 496 persons with chronic insomnia who chose or were randomized to one of three single-component behavioral therapies—sleep education and hygiene (SEH), stimulus control therapy (SCT), or sleep restriction therapy (SRT)—or a multi-component therapy (MCT) combining all three. At time of study, participants had experienced moderately severe insomnia on average for 11 years. Participants completed the measure of satisfaction within one week of treatment conclusion. The measure’s subscales assessed participants’ perception of the following attributes: suitability, utility and usefulness of mode and dose of therapy delivery; therapists’ competence and interpersonal style; and treatment outcomes. The subscales demonstrated good psychometric properties. Analysis of variance was used in the comparisons. Results. Significant differences (all p-values < .001) were found in the ratings of some process attributes and of all outcome attributes of the therapies. Education was rated as more suitable but less useful than behavioral instructions. Overall, results support patients’ satisfaction with SCT, SRT, and MCT and, to a lesser extent, with SEH as a single-component therapy. Discussion and conclusions. SCT, SRT and MCT were viewed favorably as therapies for successfully managing insomnia.